2020
DOI: 10.4081/hr.2020.8396
|View full text |Cite
|
Sign up to set email alerts
|

Surgery Results in Low Relapse and Progression Rates in Extramedullary Plasmacytoma of the Head and Neck: A Case Cohort and Review of the Literature

Abstract: Extramedullary plasmacytoma of the head and neck is a rare indolent neoplasm. Radiotherapy is often the preferred treatment option with excellent local control and survival. The risk of local recurrence or transformation to multiple myeloma is 10- 30%. In our case-cohort, thorough, sensitive initial evaluation for disseminated clonal disease and the incorporation of surgery led to excellent results with no recurrences or systemic progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Treatment is often guided by a limited number of retrospective studies involving small samples (Table 1). A recent comprehensive population-based analysis found that most SPs are highly radiosensitive and radiation dose >40 Gy is associated with improved survival and decreased recurrence [16]. There are contradictory reports of the benefits of surgery combined with adjuvant radiotherapy [9,[16][17][18].…”
Section: Case Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment is often guided by a limited number of retrospective studies involving small samples (Table 1). A recent comprehensive population-based analysis found that most SPs are highly radiosensitive and radiation dose >40 Gy is associated with improved survival and decreased recurrence [16]. There are contradictory reports of the benefits of surgery combined with adjuvant radiotherapy [9,[16][17][18].…”
Section: Case Bmentioning
confidence: 99%
“…A recent comprehensive population-based analysis found that most SPs are highly radiosensitive and radiation dose >40 Gy is associated with improved survival and decreased recurrence [16]. There are contradictory reports of the benefits of surgery combined with adjuvant radiotherapy [9,[16][17][18]. Interestingly, the prognosis of SPs is different among SMPs and SBPs due to the increased likelihood of SBP progressing to MM [19].…”
Section: Case Bmentioning
confidence: 99%
“…These tests help determine the long-term prognosis of solitary plasmacytoma and the risk of progression to multiple myeloma. Surgical treatment has shown positive outcomes in long-term prognosis, while irradiation and systemic therapy may not be recommended as standard treatment protocols [ 7 ]. Here, we present a rare case of the presence of a plasmacytoma in the upper jaw.…”
Section: Introductionmentioning
confidence: 99%